2008
DOI: 10.1017/s1727719100002136
|View full text |Cite
|
Sign up to set email alerts
|

The Theoretical and Experimental of Tube Drawing With Floating Plug for Micro Heat-Pipes

Abstract: This work presents a novel mathematical model, formed by modifying the conventional Slab Model, to predict the behaviors of tube drawing with a floating plug in the hollow copper tubes. FEM and experimentation are employed to verify the analytical solution. The model incorporates some parameters, including as die semi-angle, plug semi-angle, friction coefficient and wall thickness reduction ratio. The Self Lock Effect is simulated using FEM, and the effect is useful in estimating the critical drawing force. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The self-catching plug reduces the risk for failure during start up of the FPD process. Wang and Wang (2008) modified conventional slab model (CSM) to analysed FPD process of hollow copper tubes. They concluded that proposed model was more accurate than the CSM.…”
Section: Introductionmentioning
confidence: 99%
“…The self-catching plug reduces the risk for failure during start up of the FPD process. Wang and Wang (2008) modified conventional slab model (CSM) to analysed FPD process of hollow copper tubes. They concluded that proposed model was more accurate than the CSM.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments using a ball-type plug, different from the conventional conical plug, allowed the frequency of breaks during drawing to be reduced. Wang et al [ 26 ] proposed a new mathematical model to predict the behaviour of tube drawing with a floating plug in hollow copper tubes. This model incorporates the plug semi-angle, die semi-angle, wall thickness reduction ratio, and friction coefficient.…”
Section: Introductionmentioning
confidence: 99%